Solusi Primitif Persamaan Diophantine x^2+pqy^2=z^2 untuk bilangan-bilangan prima p dan q - Aswad Hariri Mangalaeng (Jurnal Matematika, Statistika dan Komputasi, 2022)
In this paper, we determine the primitive solutions of diophantine equations x^2+pqy^2=z^2, for positive integers x, y, z, and primes p,q. This work is based on the development of the previous results, namely using the solutions of the Diophantine equation x^2+y^2=z^2, and looking at characteristics of the solutions of the Diophantine equation x^2+3y^2=z^2 and x^2+9y^2=z^2.